Complementary results to Heuvers’s characterization of logarithmic functions - Himmel, Martin (Annales Mathematicae Silesianae, 2017)
Based on a characterization of logarithmic functions due to Heuvers we develop analogous results for multiplicative, exponential and additive functions, respectively.